2016
DOI: 10.1017/edp.2016.4
|View full text |Cite
|
Sign up to set email alerts
|

Another Path to Belonging: A Case Study of Middle School Students’ Perspectives

Abstract: This qualitative study explored students’ experiences in a small, early-college secondary school in the United States that intentionally aims to create a culture promoting accelerated academic achievement, particularly in the areas of science, technology, engineering, and math (STEM). Past research in the fields of both educational and developmental psychology has suggested that students’ sense of belonging plays a significant role in their social and academic functioning. Few studies, however, have explored h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 31 publications
0
20
0
3
Order By: Relevance
“…Conversely, Green, Emery, Sanders, and Anderman [32] found that there was a clear distinction between social and academic SOBAS. Green et al surveyed 76 middle school students and conducted nine qualitative interviews as part of a larger, longitudinal project.…”
Section: Academic Belongingmentioning
confidence: 95%
See 1 more Smart Citation
“…Conversely, Green, Emery, Sanders, and Anderman [32] found that there was a clear distinction between social and academic SOBAS. Green et al surveyed 76 middle school students and conducted nine qualitative interviews as part of a larger, longitudinal project.…”
Section: Academic Belongingmentioning
confidence: 95%
“…Academic belonging resulted from students' experiences in meeting high academic expectations, taking part in a variety of educational opportunities, obtaining academic support from teachers, and having shared academic interests with peers. There was evidence to suggest that social and academic belonging are discrete features of students' overall SOBAS; this was evident in that some students experienced one type of belonging without the other [32]. This has important implications for the connection of both academic and social belonging in school, particularly for at-risk students, where greater success is evident when both factors are in place.…”
Section: Academic Belongingmentioning
confidence: 99%
“…Paauglystės tarpsniu labiau nei kitu laikotarpiu reikalinga sava socialinė terpė, bendraamžių pripažinimas mokykloje (Green et al, 2016, Zins et al, 2004, išryškėja priklausymo, pasiekimų ir vadovavimo poreikiai (McClelland, 1988).…”
Section: Priklausymo Mokyklai Jausmo Samprataunclassified
“…Tarpusavio ryšių trūkumas gali neigiamai veikti mokinių savęs suvokimą, pasitenkinimą gyvenimu ir jų norą mokytis. Geras mokytojo ir mokinio ryšys su mokykla, mokytojais ir bendraamžiais daro įtaką mokinių polinkiui tobulėti, visavertiškai socialinės grupės narystei (Green et al, 2016, Durlak, et al, 2011.…”
Section: Priklausymo Mokyklai Jausmo Samprataunclassified
See 1 more Smart Citation